Pro-poor intervention strategies in irrigated agriculture: lessons from the Asian experience - International Water Management Institute (International Water Management Institute, 2007)
Irrigated agriculture has contributed greatly to food security in Asia - and irrigation projects present new opportunities for reducing poverty. This requires that projects deliberately tilt towards the poor. Moreover, policymakers, implementers and managers need to adopt an integrated approach when using irrigation as a pro-poor intervention strategy. With the right institutional and technical conditions, an effective incentives structure and proper implementation and management practices, pro-poor irrigation projects can make a significant difference to poverty in the region.